Lignocellulose-derived inhibitors can extend residence of Clostridium beijerinckii in active solventogenic state - Koppova, K; Burianova, L; Patakova, P; Branska, B (Bioresources and bioprocessing, 2025)
Lignocellulose is a promising renewable resource for producing platform chemicals, such as acetone, butanol, and ethanol, via ABE fermentation by solventogenic clostridia. This study investigates the effects of common lignocellulose derived inhibitory compounds: ferulic acid, coumaric acid, and furfural on Clostridium beijerinckii. Dual-staining with propidium iodide and CFDA, combined with flow cytometry, was employed to assess physiological variability. The results showed that phenolic acid-induced stress helped maintain a higher proportion of viable cells during the production phase, enhancing solvent yields and reducing sporulation. At 0.4 g/L, ferulic and coumaric acids did not reduce cell viability; however, coumaric acid exposure led to an acid-crash profile. Conversely, a more robust inoculum exposed to both phenolic acids simultaneously exhibited effects similar to ferulic acid alone, including slower viability decline, reduced growth and sporulation, and improved solvent production. Furfural exposure at 1.5 g/L resulted in immediate viability loss in 20% of the population, though the overall decline accompanied by the highest sporulation rate occurred later than in the control. Additionally, furfural transformation was slower, suppressing butyrate production and reducing solvent production by 13%. This study suggests that delaying cell death mechanism may explain the stimulatory effects of inhibitors, advancing lignocellulose use in the future.
Keywords: Butanol; Clostridium beijerinckii; ABE; Viability; Lignocellulose inhibitors; Carboxyfluorescein diacetate; Cytometry